2021
DOI: 10.1186/s12870-021-02960-4
|View full text |Cite
|
Sign up to set email alerts
|

Pinpointing regulatory protein phosphatase 2A subunits involved in beneficial symbiosis between plants and microbes

Abstract: Background PROTEIN PHOSPHATASE 2A (PP2A) expression is crucial for the symbiotic association between plants and various microbes, and knowledge on these symbiotic processes is important for sustainable agriculture. Here we tested the hypothesis that PP2A regulatory subunits, especially B’φ and B’θ, are involved in signalling between plants and mycorrhizal fungi or plant-growth promoting bacteria. Results Treatment of tomato plants (Solanum lycopers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…An interesting study has revealed that low levels of B′φ transcripts are necessary for the proper formation of mycorrhizal associations in tomato roots to maintain normal plant development [ 55 ].…”
Section: Roles and Functioning Of B Subunitsmentioning
confidence: 99%
“…An interesting study has revealed that low levels of B′φ transcripts are necessary for the proper formation of mycorrhizal associations in tomato roots to maintain normal plant development [ 55 ].…”
Section: Roles and Functioning Of B Subunitsmentioning
confidence: 99%
“…A fifth clade, Φ, is also found in higher plants, but not in Arabidopsis, and appears to be involved in the interaction with mycorrhizal fungi. Arabidopsis and other Brassicaceae/Cleomaceae do not form mycorrhizal associations, and this could be the reason that B'φ has been lost from Arabidopsis [9,14,15]. The B' clades evolved after the division of eukaryotes into animals and plants, and there is no connection between the use of Greek letters for animal and plant B' subunits.…”
Section: B' Structure and Recognition Of Slim Motifsmentioning
confidence: 99%